2018
DOI: 10.1097/ico.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Meibomian Gland Squeezer for Treatment of Meibomian Gland Dysfunction

Abstract: The meibomian gland squeezer may be safe, effective, and helpful for treatment of MGD and may offer an attractive treatment option for some patients with MGD, although it can cause mild pain or discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 51 publications
3
35
0
2
Order By: Relevance
“…By contrast, our treatment procedure was standardized and performed by the doctor. Compared with other in-door treatment methods (Zhao et al, 2016;Syed and Sutula, 2017;Wang et al, 2018;Aketa et al, 2019), the device we used has the advantages of being less invasive, lower cost, and more convenient. It is easily managed because of its electric characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, our treatment procedure was standardized and performed by the doctor. Compared with other in-door treatment methods (Zhao et al, 2016;Syed and Sutula, 2017;Wang et al, 2018;Aketa et al, 2019), the device we used has the advantages of being less invasive, lower cost, and more convenient. It is easily managed because of its electric characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…50 However, in spite of the pain, several studies have demonstrated the efficacy of manual meibomian gland expression for the treatment of MGD. [51][52][53] It is recommended that the procedure be performed once a month until the gland dysfunction is resolved. 2 Although expression of meibomian glands appears to be safe and effective, its evaluation by observer-masked, randomised, controlled trials is necessary, as is the development of new technologies that can achieve such expression with reduced pain.…”
Section: Manual Expression Of Meibomian Glandsmentioning
confidence: 99%
“…2011 The amount of force required to express obstructed glands can be substantial and is usually limited by the associated pain 2011. However, in spite of the pain, several studies have demonstrated the efficacy of manual meibomian gland expression for the treatment of MGD 2018. It is recommended that the procedure be performed once a month until the gland dysfunction is resolved 2011.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Recently, many kinds of treatments for DED have been proposed, such as Meibomian gland squeezer, polyunsaturated fatty acids, omega-3 fatty acids, perfluorohexyloctane, chitosan-N-acetylcysteine (C-NAC) and retinol palmitate [186][187][188][189][190][191]. In terms of omega fatty acids, studies demonstrated that ω-3 and ω-6 fatty acids can act directly on human Meibomian gland epithelial cells to influence the quality and quantity of intracellular lipids [192].…”
Section: Other Potential Agentsmentioning
confidence: 99%